Engine cycle analysis using an ideal gas with constant specific heats as a working fluid - Quiros, Edwin N.
This work presents the results of computer modeling of the basic and idealized engine cycles assuming the working fluid to be an ideal gas with constant specific heats. The various processes that constitute the engine cycles are assumed to be ideal. A thermodynamic analysis of the engine cycles is performed to calculate performance parameters. Parametric studies using the computer model was conducted to determine desired engine design and operating conditions.